PENINGKATAN PENGETAHUAN FUNGSI KOGNITIF DI POSBINDU KENANGA II JATIMELATI PONDOK MELATI BEKASI - Rifaa Septyani; Dwi Agustina; Nur Achirda; Ariz Muhammad Laitupa; Azkiya Azzahra; Indah Cahyani; Nufal Zeni Mubarakh (IFI cabang Kota Bekasi, 2023)
Introduction: Over the last several decades, the number of elderly has continued to grow, resulting in increasing health problems for the elderly, including cognitive function decline. The results of problem identification showed that the elderly at Posbindu Kenanga II was suffering from a decline in cognitive function. Therefore, the focus of community service activities was to address cognitive functions. Method: Community service activities were carried out at Posbindu Kenanga II Jatimelati Pondok Melati Bekasi from February to April 2023 with a target of 28 elderly. The phases of the community service included problem identification, counseling/education, brain gym exercise, and evaluation. MOCA was used to assess cognitive function, while a questionnaire was used to assess knowledge. Results: The average knowledge before and after community service increased from 7.00 to 8.82 with a p-value of 0.000. Conclusion: Community service activities significantly increased knowledge of cognitive functions in the elderly. For this reason, this activity should be continued on an ongoing basis in order not only to increase knowledge but also to affect cognitive function. Keywords: Elderly, Cognitive, Knowledge, Health Education and Promotion